Badiiy matnda leksik birliklarning poetik imkoniyatlari - Abdurashidova, Iroda (FILOLOGIYA UFQLARI JURNALI, 2021)
Poetic possibilities of lexical units in the literary text (on the example of Hamid Olimjon and Zulfiya)